2000
DOI: 10.1038/80655
|View full text |Cite
|
Sign up to set email alerts
|

BDNF upregulation during declarative memory formation in monkey inferior temporal cortex

Abstract: In primates, visual long-term memory of objects is presumably stored in the inferior temporal (IT) cortex. Because brain-derived neurotrophic factor (BDNF) is involved in activity-dependent neural reorganization, we tested the hypothesis that BDNF would be upregulated in IT cortex during formation of visual pair-association memory. To eliminate genetic and cognitive variations between individual animals, we used split-brain monkeys for intra-animal comparison in PCR-based mRNA quantitation. The monkeys learned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 49 publications
6
90
0
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) mRNA is selectively induced in a focal patch within A36 during memory formation (26). Lesion studies demonstrated a functional double dissociation where the PRh cortex is engaged in a mnemonic processing, whereas area TE is devoted to a perceptual processing (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) mRNA is selectively induced in a focal patch within A36 during memory formation (26). Lesion studies demonstrated a functional double dissociation where the PRh cortex is engaged in a mnemonic processing, whereas area TE is devoted to a perceptual processing (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical distribution of BDNF mRNA in the adult human DLFPC observed in our study is in good agreement with previous reports in the primate neocortex that show prominent but uneven expression of BDNF mRNA in cortical pyramidal neurons of layers III, V, and VI. 47,56,57 Three nonmutually exclusive models could explain the BDNF reduction in pyramidal neurons of the DLFPC of patients with schizophrenia: (1) BDNF is reduced as an epiphenomenon of having a chronic mental illness and/or because of antipsychotic drug treatment of patients with schizophrenia, (2) BDNF expression is altered in patients with schizophrenia because of the more frequent inheritance of an altered BDNF 'gene', and (3) BDNF fails to be induced during normal brain development because of complex genetic and/or environmental signals, which interact to impair the normal development of the DLFPC in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, we noted that BDNF mRNA was not expressed uniformly in all cortical neurons ( Figure 5), consistent with reports in the monkey cortex. 56,57 Therefore, cell-based quantitation was undertaken as a more sensitive way to measure BDNF expression levels between the two subject groups.…”
Section: Bdnf In Situ Hybridizationmentioning
confidence: 99%
“…More recently, BDNF/ TrkB signaling has been implicated in learning and memory by directly examining its role in a variety of learning paradigms in behaving animals. Despite the fact that BDNF has been shown to play a critical role in a variety of learning paradigms in mice Qiao et al 1998;Aloe et al 1999;Croll et al 1999;Horger et al 1999), monkeys (Tokuyama et al 2000), zebra finches (Akutagawa and Konishi 1998;Wade 2000), and chicks (Johnston et al 1999;Johnston and Rose 2001), the behavioral tests used in those studies were not as hippocampal-dependent as spatial learning or contextual fear conditioning. We focus here on behavioral evidence obtained using specific hippocampal-mediated spatial learning and contextual fear conditioning paradigms.…”
Section: Bdnf Signaling Is Necessary For Hippocampal-dependent Learningmentioning
confidence: 99%